Problem of pollution of occupational lead in the laboratories of fire assay of gold minerals - Peragallo Barrios, Victor Hugo (2019)
Occupational lead contamination in Peru is a serious problem that has not been adequately regulated in Peru to date. The main activities that generate occupational contamination of this metal include processes such as battery manufacturing, lead scrap smelting, fire testing to quantify gold and silver in mining, etc. The Objective of this article is to identify the details that should be considered in the Lead contamination in fire assay laboratories in the analytical determination of gold and silver, and analyze their deficiencies. Data on lead contamination in fire test laboratories in Peru are difficult to find in the literature available.